Recent developments in 'low cost carrier' research: a review. (2018) - Yadav, Manish; Dhingra, Tarun
Recent trends in the low cost carrier (LCC) literature is reviewed in this study from 2005-2015. On the basis of systematic review, 169 articles located in 20 top air transport journals are categorised into nine distinct topics/major themes: 1) airline strategy ; 2) airline business model ; 3) airline economics ; 4) airline performance ; 5) airline market structure ; 6) airline operations ; 7) airline sales and marketing ; 8) airline service quality ; 9) airline and airport relationship . All themes are reviewed and their intra linkages are presented in the study. Concluding thoughts concerns requirement to carry out process and variance-based studies and compare various LCC models across the word from the point of view of location, policy, regulations and competition through process and variance-based research.